A new species of Ptychochromis from southeastern Madagascar (Teleostei: Cichlidae) - Martinez, Christopher M.; Arroyave, Jairo; Sparks, John S. (Zootaxa, 2015)
We describe a new species in the endemic Malagasy cichlid genus Ptychochromis. Ptychochromis mainty, new species, is known from four individuals, all collected in the Fort Dauphin region of southeastern Madagascar, and shares a palatine morphology (eastern-type palatine) with other eastern congeners. Ptychochromis mainty is distinguished from all congeners by a nearly uniform dark brown to black pigmentation pattern in preservation and by the presence of a relatively continuous and expansive black longitudinal midlateral blotch in life, extending from the posterior margin of the opercle to the caudal peduncle. The new species is further distinguished from other eastern Ptychochromis species by having minimal or no overlap of the first supraneural with the dorsoposterior region of the supraoccipital crest (vs. marked overlap). We present a molecular-based phylogeny for all available Ptychochromis species, which supports the hypothesis that P. mainty is a distinct taxon. The new species is recovered as the sister taxon to P. grandidieri within a clade comprising species with an eastern-type palatine morphology. We present a geometric morphometric analysis that provides additional evidence to distinguish P. mainty from congeners.